2016
DOI: 10.1007/s12325-016-0338-1
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical and Biological Principles of Cold Atmospheric Plasma Application in Skin Cancer

Abstract: Plasma-based electrosurgical devices have long been employed for tissue coagulation, cutting, desiccation, and cauterizing. Despite their clinical benefits, these technologies involve tissue heating and their effects are primarily heat-mediated. Recently, there have been significant developments in cold atmospheric pressure plasma (CAP) science and engineering. New sources of CAP with well-controlled temperatures below 40 °C have been designed, permitting safe plasma application on animal and human bodies. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
81
1
15

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 120 publications
(99 citation statements)
references
References 81 publications
2
81
1
15
Order By: Relevance
“…In the present study, CAP treated PBS showed increasing levels of nitrated, nitrite as well as H 2 O 2 , and the concentrations of nitrate and nitrite were much higher than H 2 O 2 . As we know, CAP is able to induce many types of cancer cell death by production of many different kind of reactive species, such as superoxide(O 2 −), Hydroxyl superoxide (HO 2 −), Hydroxyl radical (·OH), hydrogen peroxide (H 2 O 2 ), nitric oxide (NO), nitrogen dioxide (NO 2 ) nitrous oxide(N 2 O), and so on . Here, our data confirmed that CAP could induced melanoma cell line A375 and A875 apoptosis.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…In the present study, CAP treated PBS showed increasing levels of nitrated, nitrite as well as H 2 O 2 , and the concentrations of nitrate and nitrite were much higher than H 2 O 2 . As we know, CAP is able to induce many types of cancer cell death by production of many different kind of reactive species, such as superoxide(O 2 −), Hydroxyl superoxide (HO 2 −), Hydroxyl radical (·OH), hydrogen peroxide (H 2 O 2 ), nitric oxide (NO), nitrogen dioxide (NO 2 ) nitrous oxide(N 2 O), and so on . Here, our data confirmed that CAP could induced melanoma cell line A375 and A875 apoptosis.…”
Section: Discussioncontrasting
confidence: 96%
“…It was hypothesized that such an effect was related to reduced expression of cell cycle mediators (eg, cyclins D1, E1 and E2), as well as increased expression of the cell cycle suppressor protein, p27KIP1 . Cold atmospheric plasma (CAP) with well‐controlled temperatures below 40°C has recently been developed with the use of new sources . In preliminary studies of this system, D 2 O + N 2 plasma jets and a helium CAP torch were shown to induce apoptosis of melanoma cells .…”
Section: Introductionmentioning
confidence: 99%
“…[1] CAP treatment has been used to inactivate bacteria, [2] enhance blood coagulation, [3] promote cancerous cell apoptosis, [4] and promote wound healing [5] in recent years. (b) Cold atmospheric plasma (CAP) device using helium as the plasma forming gas.…”
mentioning
confidence: 99%
“…[25][26][27] Many studies have provided evidence that cytotoxic effects of plasma in different cancer and/or non-cancer cell lines differ significantly among each other. [28][29][30] Besides the traditional explanation of an altered redox balance, [12] detailed investigation on molecular mechanisms underlying these differences-especially with regard to plasma-is scarce. In a previous comparison of metabolic activity between seven different cell lines, Jurkat were most and THP-1 cells least affected by plasma.…”
mentioning
confidence: 99%